Pengaruh Kualitas Pelayanan, Fasilitas dan Lokasi terhadap Kepuasan Tamu New Puri Garden Hotel Semarang - Ferry Gunawan Prasetyo; Ida Martini Alriani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine the influence of service quality, facilities, and location on guest satisfaction at New Puri Garden Hotel Semarang. In the increasingly competitive hospitality industry, understanding the factors that influence guest satisfaction is crucial for enhancing customer loyalty and business competitiveness. This research uses a quantitative approach with a survey method. The population in this study consisted of all guests staying at New Puri Garden Hotel Semarang, totaling 97 individuals. The sampling technique used was random sampling, where the entire population was taken as the sample, resulting in 97 respondents. The research instrument was a questionnaire designed based on indicators of each variable. The data analysis technique employed was multiple linear regression analysis to examine the effect of independent variables (service quality, facilities, and location) on the dependent variable (guest satisfaction). The results of the analysis show that service quality has a positive and significant effect on guest satisfaction. This is evidenced by the t-value of 3.702, which is greater than the t-table value of 1.660, with a significance value of 0.005 (< 0.05). Facilities also have a positive and significant influence on guest satisfaction, with a t-value of 3.118 > 1.660 and a significance value of 0.002 (< 0.05). Meanwhile, location has the strongest influence on guest satisfaction, with a t-value of 6.468 > 1.660 and a significance value of 0.000 (< 0.05). Based on these results, it can be concluded that partially, the three variables—service quality, facilities, and location—have a positive and significant effect on guest satisfaction. These findings indicate that improving service quality, providing adequate facilities, and choosing a strategic location are essential factors in creating a satisfying guest experience. Therefore, hotel management should prioritize the development and enhancement of these three aspects to maintain and increase customer satisfaction in a sustainable manner.